Plant’s developmental decision to either abort a flower or set seed - Dinesh Kumar Saini; Juliana M. Espíndola Lima; Ramanjulu Sunkar; Colleen Doherty; Krishna S.V. Jagadish (Trends in Plant Science, 2026)

Transcriptomic analysis reveals time-of-day-specific genes and gene regulatory networks in response to chilling stress in sorghum - Kanjana Laosuntisuk; Amaranatha Vennapusa; Impa M. Somayanda; S. V. Krishna Jagadish; Colleen J. Doherty (Plant Physiology Reports, 2025)
Sorghum is a versatile crop with many uses, ranging from human consumption to biofuel production. In the U.S., sorghum experiences heat stress during flowering in the summer. Several strategies have been developed to reduce yield loss caused by heat stress. One of the most reliable strategies is ‘heat escape’, in which early-season planting shifts the crop’s reproductive phase to occur before heat stress exposure. However, this heat escape strategy is limited due to sorghum’s sensitivity to early-season chilling. In sorghum, early-season chilling stress negatively affects seed germination, emergence, and seedling vigor. Candidate chilling-tolerant genes in sorghum have been proposed, but the molecular mechanisms of the candidate genes in chilling stress response have not been well established. We hypothesized that many transcriptional responses critical for sorghum’s response to low temperature have been missed by not examining gene expression at multiple times throughout the day. Here, we investigated the effect of chilling stress and time of day on transcriptional responses using 3′ RNA-Seq. We found that time-of-day gated gene expression in response to chilling stress results in various transcriptional response patterns, each with unique biological processes. Weighted gene correlation network analysis (WGCNA) identified modules of transcripts that are specifically responsive to nighttime chilling. Candidate regulatory transcription factors (TFs) of the chilling stress response in sorghum were identified through gene regulatory network analysis. Our results demonstrate that the time of day samples are collected substantially affects our understanding of chilling tolerance, and suggest that a full capture of the network of chilling stress responses requires an examination of multiple times of day. By profiling transcription across different times of day under chilling conditions, we identify regulatory programs that can be leveraged to expand early-planting windows.

A Tale of Two Tails: Untangling the Phylogeography and Demographic History of Extant Species of Mulgara ( Dasycercus spp.) in the Australian Arid Zone - Aline Gibson Vega; Brenton von Takach; Linette Umbrello; Dympna Cullen; Mark Cowan; Helen Crisp; Chris Dickman; Tim Doherty; William La Marca; Jenny Molyneux; Colleen Sims; Peter B. S. Spencer; et al. (Journal of Biogeography, 2025)
Aim Australia's arid and semi‐arid zones cover about 70% of the continent, yet our understanding of the biogeography of these diverse and expansive landscapes remains limited. Mulgara ( Dasycercus spp.; Marsupialia: Dasyuridae), a widely distributed mammal taxon, offers an opportunity to explore patterns of the population structure across the region, previously hampered by taxonomic confusion surrounding extant species. Here, we aimed to (1) clarify the current distribution of extant Dasycercus lineages, (2) describe the population genomic structure of the widespread brush‐tailed mulgara, and (3) determine whether observed patterns of population genomic structure in brush‐tailed mulgara are consistent with biogeographic breaks. Location Arid and semi‐arid regions of Australia. Taxon Two species are extant; the brush‐tailed mulgara ( D. blythi ) and the crest‐tailed mulgara ( D. hillieri , previously D. cristicauda ). Methods We sampled individuals from contemporary and museum tissue collections, obtaining next‐generation sequencing data for 311 individuals, retaining 4360 single‐nucleotide polymorphisms (SNPs) for population genomic analysis. Results We found that the two extant species are clearly delineated, corresponding well to current understanding of their respective distributions. The population genomic substructure in the brush‐tailed mulgara (211 samples, 2740 SNPs) aligns primarily with major drainage divisions. Inference of historical population size change indicated that all populations have likely had stable population sizes for much of the past 1000 years, although post‐European colonisation declines in some populations cannot be ruled out. The Pilbara population was most differentiated from other populations and displayed a stronger pattern of isolation‐by‐distance. Nevertheless, observed heterozygosity was similar across each of the populations ( H o = 0.078–0.090). Conclusions Stable population dynamics linked to the ecology of the mulgara and their high dispersal potential likely explain consistent levels of genetic diversity across most populations, but the effects of geography, such as major drainage divisions, drive the apparent contemporary population structure. Additional targeted tissue collection in under‐sampled regions is recommended to better quantify genomic diversity, structure, and genetic health across the species' full range.

Auxin–cytokinin interplay shapes root functionality under low-temperature stress - Manish Tiwari; Ritesh Kumar; Senthil Subramanian; Colleen J. Doherty; S.V. Krishna Jagadish (Trends in Plant Science, 2023)

Only a matter of time: the impact of daily and seasonal rhythms on phytochemicals - Donna J. Liebelt; Juliette T. Jordan; Colleen J. Doherty (Phytochemistry Reviews, 2019)

Novel transcriptional responses to heat revealed by turning up the heat at night - Dmitry O. Grinevich; Jigar S. Desai; Kevin P. Stroup; Jiaqi Duan; Erin Slabaugh; Colleen J. Doherty (Plant Molecular Biology, 2019)